A place to gather: the roof terrace of the Marseilles Housing Block - Sequeira, Marta (Le Corbusier: Architecture, Urbanism and Theory, 2009)
[Intervenção apresentada no congresso internacional Le Corbusier: Architecture, Urbanism and Theory] Southern Polytechnic State University